HUBUNGAN ANTARA PENGETAHUAN DENGAN LUARAN TERAPI PADA PASIEN DIABETES MELLITUS TIPE 2-DISLIPIDEMIA - Faridah, Imaniar Noor; Dania, Haafizah; Saputri, Ginanjar Zukhruf; A, Faiza Chusnuni (Jurnal Farmasi Indonesia, 2019)
Diabetes mellitus and dyslipidemia are non communicable disease which those prevalence increased significantly.Those are risk factors of cardiovascular disease. A good knowledge is important to enhance the awareness of disease, so that the target of outome therapy can be achieved. The aim of this research are to describe the patient?s knowledge about the disease and to know the relationship between patient?s knowledge and outcomes therapy (HbA1c and total cholesterol). This research is an observational analytic study with cross setional design. The data taken prospectively from diabetes patients in PKU Muhammadiyah Hospital around September to December 2016. Sample who met the inclusion criterias were patient who diagnosed with diabetes mellitus-dyslipidemia, aged over 18 years old, have a HbA1c and total cholesterol data and using minimal 2 drugs, antidiabetic and anticholesterol. The datas are the knowledge data which taken using validated questionnaire and the outcomes therapy which taken from patient?s medical data. Linear regression analysis is done to know the relationship between knowledge and outcome therapy. Around 37 patients who participated in this research were below 60 years old (64.9%), mostly female (59.5%), and have en education more than 9 years (86.5%). Besides that, only 62.2% patient who achieved the target of HbA1c, and only 56.8% patient who achieved the target of total cholesterol. Furthermore, based on linear regression analysis showed that there was no relationship between knowledge and outcome therapy either HbA1c or total cholesterol (sig 0.893 and 0.292).